2000
DOI: 10.1074/jbc.c000156200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Folding Rates of Homologous Prokaryotic and Eukaryotic Proteins

Abstract: The rate of polypeptide chain elongation is up to one order of magnitude faster in prokaryotic cells than in eukaryotes. Here we report that the rates of in vitro refolding of orthologous prokaryotic and eukaryotic proteins correlate with their differential rates of biosynthesis. The mitochondrial and cytosolic aspartate aminotransferases of chicken and aspartate aminotransferase of Escherichia coli show pairwise sequence identities of 41-48% and nearly identical three-dimensional structures. Nevertheless, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
(14 reference statements)
0
25
0
2
Order By: Relevance
“…Such a slow increase in fluorescence is unlikely to be monitoring a conformational change associated with the early stages of folding (for review see Refs. [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Such a slow increase in fluorescence is unlikely to be monitoring a conformational change associated with the early stages of folding (for review see Refs. [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Unfolding-It has been reported that the rate of refolding of chicken cAAT and mAAT decreased by a factor of 4 and 25, respectively, when the proteins were denatured in 6 M GdnHCl for 40 s instead of for 40 min (29). These results were interpreted as indicating that proline isomerization is the ratelimiting step in the slow refolding of these enzymes unfolded for long periods of time.…”
Section: Reactivation Kinetics Of Plp-maat After Different Times Ofmentioning
confidence: 98%
“…These steps follow the rapid collapse of the unfolded chain into a molten globule-like intermediate. It has been proposed that isomerization of the two cis-prolines in AAT is responsible for the two slow phases observed during in vitro refolding of chicken mAAT (29) or E. coli AAT (30). However, analysis of the folding properties of P138A and P195A mutants of E. coli AAT indicated that although proline isomerization may play some role, other conformational rearrangements must rule the folding of this protein (31,32).…”
mentioning
confidence: 99%
“…Proline Isomerization and Folding of PmMDH-Comparative folding studies between homologous prokaryotic and eukaryotic aspartate transaminase performed by Widmann and Christen (14) indicate that the slower folding rate of the mitochondrial enzyme is caused, in part, by differences in proline isomerization (14). A sequence comparison between EcMDH and PmMDH reveals that there are more proline residues present within the mitochondrial primary sequence than in its bacterial homolog (21 versus 13 prolines, respectively).…”
Section: Refolding Reactions Of Ecmdh With Pmmdh At Physiological Temmentioning
confidence: 99%
“…In the absence of chaperonins, EcMDH has been found to reactivate much more rapidly than PmMDH at 25°C (14). In this study, we have examined the refolding of EcMDH at a physiological temperature of 37°C to determine whether Ec-MDH will now require chaperonins to aid in its folding.…”
mentioning
confidence: 99%